Vaccines against candidiasis: Status, challenges and emerging opportunity - Sahu, Satya Ranjan; Bose, Swagata; Singh, Manish; Kumari, Premlata; Dutta, Abinash; Utkalaja, Bhabasha Gyanadeep; Patel, Shraddheya Kumar; Acharya, Narottam (Frontiers in Cellular and Infection Microbiology, 2022)
Candidiasis is a mycosis caused by opportunistic Candida species. The occurrence of fungal infections has considerably increased in the last few years primarily due to an increase in the number of immune-suppressed individuals. Alarming bloodstream infections due to Candida sp. are associated with a higher rate of morbidity and mortality, and are emerged as major healthcare concerns worldwide. Currently, chemotherapy is the sole available option for combating fungal diseases. Moreover, the emergence of resistance to these limited available anti-fungal drugs has further accentuated the concern and highlighted the need for early detection of fungal infections, identification of novel antifungal drug targets, and development of effective therapeutics and prophylactics. Thus, there is an increasing interest in developing safe and potent immune-based therapeutics to tackle fungal diseases. In this context, vaccine design and its development have a priority. Nonetheless, despite significant advances in immune and vaccine biology over time, a viable commercialized vaccine remains awaited against fungal infections. In this minireview, we enumerate various concerted efforts made till date towards the development of anti-Candida vaccines, an option with pan-fugal vaccine, vaccines in the clinical trial, challenges, and future opportunities.